A Randomized Double Blind Controlled Safety Trial Evaluating D-Lactic Acid Production in Healthy Infants Fed a Lactobacillus reuteri-containing Formula. (January 2014) - Papagaroufalis, Konstantinos; Fotiou, Aikaterini; Egli, Delphine; Tran, Liên-Anh; Steenhout, Philippe
Background: D-Lactic acidosis in infants fed lactic acid bacteria-containing products is a concern. Methods: The primary objective of this non-inferiority trial was to compare urinary D-lactic acid concentrations during the first 28 days of life in infants fed formula containing Lactobacillus reuteri (1.2 x 10 6 colony forming units (CFU)/ml) with those fed a control formula. The non-inferiority margin was set at a two-fold increase in D-lactic acid (0.7 mmol/mol creatinine, log-transformed). Healthy term infants in Greece were enrolled between birth and 72 hours of age, and block randomized to a probiotic ( N = 44) or control ( N = 44) group. They were exclusively fed their formulae until 28 days of age and followed up at 7, 14, 28, 112, and 168 ± 3 days. Anthropometric measurements were taken at each visit and tolerance recorded until 112 days. Urine was collected before study formula intake and at all visits up to 112 days and blood at 14 days. Results: D-Lactic acid concentration in the probiotic group was below the non-inferiority margin at 28 days: treatment effect -0.03 (95% confidence interval [CI]: [-0.48 to 0.41]) mmol/mol creatinine but was above the non-inferiority margin at 7 and 14 days–-treatment effect 0.50 (95% CI: [0.05-0.96]) mmol/mol creatinine and 0.45 (95% CI: [0.00-0.90]) mmol/mol creatinine, respectively. Blood acid excess and pH, anthropometry, tolerance, and adverse events (AEs) were not significantly different between groups. Conclusion: Intake of L. reuteri -containing formula was safe and did not cause an increase in D-lactic acid beyond two weeks. Trial Registration: ClinicalTrials.gov NCT01119170.